Please write your questions in english. Anyway, if google translate got it right, you're looking for two numbers a and b, with ratio 3 and sum -16.
From the information about the ratio, we can deduce
![(a)/(b) =3 \implies a = 3b](https://img.qammunity.org/2019/formulas/mathematics/middle-school/y7n5m6r948ncxnztqlopdv4pnqrvox61ff.png)
Plug this expression inside the one of the sum to get
![a+b = -16 \implies 3b+b = -16 \implies 4b = -16 \implies b = -4](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2b2799q9htupi21tuna8u7ci26lkcdutsx.png)
And since
, we have
![a = 3(-4) = -12](https://img.qammunity.org/2019/formulas/mathematics/middle-school/aovc3hv8zo1mvcutcy6htctw96n4vrjmfh.png)